1980
DOI: 10.1111/j.1399-0004.1980.tb02292.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrafamilial associations of cholesterol and triglyceride among related and unrelated household members

Abstract: The purpose of this report was to assess intrafamilial associations of lipids between related and unrelated household members seen in the course of a population‐based survey of lipids in schoolchildren and their parents. Fasting plasma total cholesterol and triglyceride levels were measured in 6,857 children and 3,079 adults. Age effects were removed for each sex‐race group using a third‐degree polynomial regression of lipid on age; the residuals were then used as observations in the analyses. For both cholest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

1980
1980
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…Lipid levels are under genetic control and several genetic variants have been identified as being associated with lipids and the risk of cardiovascular events in the same subjects . An intrafamilial aggregation of lipid profiles has also been reported and this appears to be stronger between related than unrelated members , therefore supporting a role for genetic influences. However, there is limited information as to whether the same is true in patients with diabetes, given the strong modulation of lipid levels by glycemic control .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipid levels are under genetic control and several genetic variants have been identified as being associated with lipids and the risk of cardiovascular events in the same subjects . An intrafamilial aggregation of lipid profiles has also been reported and this appears to be stronger between related than unrelated members , therefore supporting a role for genetic influences. However, there is limited information as to whether the same is true in patients with diabetes, given the strong modulation of lipid levels by glycemic control .…”
Section: Discussionmentioning
confidence: 99%
“…In the general population, lipid and lipoprotein levels appear to be genetically determined traits with an estimated heritability of 0.5 to 0.6 . The influence of genetic factors in modulating lipid levels is supported by the intrafamilial aggregation of lipid profiles and by genome‐wide association studies, which have identified up to 95 genetic loci associated with lipid levels . However, there are scant data on the role of familial/genetic factors in modulating lipid levels in patients with type 1 diabetes (T1D), in whom glycemic control is an important determinant of dyslipidemia .…”
mentioning
confidence: 99%
“…El Family Study, de 1980, encontró una correlación positiva y fuertemente significativa de colesterolemia entre los padres y los hijos biológicos, que estaba relacionada con factores genéticos. 21 Se podría suponer que una estrategia de detección basada en este concepto se podría extrapolar a todo el núcleo familiar consanguíneo y combinar, de esa manera, el tamizaje selectivo con un test en cascada.…”
Section: Discussionunclassified
“…The Family Study, conducted in 1980, found a positive, strongly significant correlation in the blood cholesterol of parents and their biological children, which was related to genetic factors. 21 It may be assumed that a detection strategy based on this concept may be extrapolated to the entire blood relative unit and, therefore, selective screening may be combined with cascade screening.…”
Section: Discussionmentioning
confidence: 99%